VD_FINDINFO Jug / 2025 / 198 vom 28. November 2022 - VD Tribunal cantonal (2022)
CHEVAL, LOI FÉDÉRALE SUR LA PROTECTION DES ANIMAUX, NÉGLIGENCE, SURSIS À L'EXÉCUTION DE LA PEINE | 106 CP, 42 al. 1 CP, 42 al. 4 CP, 26 al. 2 LPA